Pengaruh Model Problem Based Learning (PBL) Berbantuan Media Konkret MEDAROREMI terhadap Hasil Belajar IPAS pada Siswa Kelas VI SDN 1 Awirarangan - Gina Faojina; Dewi Eka Rani; Deby Nuraisyah; Ina Setiawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low student learning outcomes in the Natural and Social Sciences (IPAS) subject are a common issue in elementary schools. This study aimed to determine the effect of the Problem-Based Learning (PBL) model, supported by the concrete learning aid MEDAROREMI (Media for the Impact of Earth's Rotation and Revolution), on the IPAS learning outcomes of Grade VI students at SDN 1 Awirarangan regarding Chapter 5, Sub-chapter B: The Impact of Earth's Rotation and Revolution. A quantitative research method employing a pre-experimental